7: Health Resource Use Following Neonatal Discharge of Extremely Preterm Infants in Canada. Issue 6 (1st June 2014) - Cross, S; Pillay, T; Luu, T; McGuire, M; Synnes, A; de Cabo, C; Dow, K; Majnemer, A; Ballantyne, M
Abstract: BACKGROUND: Preterm birth conveys an increased risk of medical and development problems, which may translate into higher health resource utilization. Resource use has not been described among preterm born infants in Canada. OBJECTIVES: To describe health resource use including health technology aides, medication and community referrals in infants born prematurely and examine factors associated with use. DESIGN/METHODS: A total of 818 preterm infants born <29 weeks gestation between January 1 to December 31, 2010, and seen at a Canadian Neonatal Follow-Up site at 18 to 22 months' corrected age (CA) were studied. Data was collected through chart review and parental interview using standardized forms. The associations between health resource use child/family characteristics were assessed by Pearson χ 2 analyses or Fisher's exact test and by ANOVA F-test for continuous variables. RESULTS: Between NICU discharge home and the 18-month CA visit, 181 infants (22%) utilized various aides in the home: supplemental oxygen (n=112), pulse oximeter (n=37), CPAP (n=8), tracheostomy (n=7), tube feeding (n=60), braces (n=42) and walker (n=10). Aid use decreased from 68.8% for infants born ≤23 weeks' gestational age (GA) to 37.5% at 24 weeks' GA and 17.5% at 28 weeks' GA. More than one-half (56.2%) received regular medication in the three months preceding the 18-month visit, including 20% on inhalers, 32% on vitamins, 17.5% on antibiotics, 5% on anti-reflux treatment and 2% on anti-convulsants. Longer time to neonatal discharge was associated with health resource use. Children with technology dependence were also more likely to be neurologically abnormal at 18 months' CA (30% vs. 6%; P<0.01) and to have foster parents (4.6% vs. 1.3%; P=0.01) and slightly more were on social welfare (12% vs. 8%). Most infants (78.6%) were referred to an allied health professional (Table 1 ) CONCLUSIONS: A substantial number of extremely preterm infants require various health care resources. The association between health technology dependence and social disadvantage warrants further investigation as this may indicate that families of medically fragile children need more support.